Analisis Biaya Obat Antihipertensi pada Pasien Rawat Jalan Peserta JKN - Nadia Pentamitta Pandji (Jurnal Sehat Mandiri, 2026)
Hypertension is a major cause of death and includes non-communicable diseases. Hypertension requires a long treatment time so that the cost of antihypertensive drugs is high. This study aims to determine the average cost of antihypertensive therapy drugs, and other cost components that cause antihypertensive costs to increase as well as the factors that affect the cost of antihypertensive drugs. The research method used is a non-experimental approach with a cross-sectional quantitative design. Data were collected using the non-probability sampling method using purposive sampling on outpatient hypertensive patients participating in JKN in 2021. Data were analyzed descriptively and statistically tested using SPSS version 20 with the Kolmogorov-Smirnov test. The average cost of antihypertensive drugs and the total cost for outpatients at Tugurejo Hospital, Central Java Province in 2021 is Rp. 37.183 and Rp. 25.394. The average cost of hypertension medication that must be disbursed each month for a single drug, a combination of 2 drugs, a combination of 3 drugs, and a combination of 4 drugs is Rp. 12.306, Rp. 35.002, Rp. 61.372, and Rp. 117.693. The average total cost of components other than antihypertensive drugs is Rp. 216.211. Statistical analysis results showed that gender did not affect drug costs or total costs. Age significantly influenced drug costs but not total costs. The number of comorbidities significantly influenced drug costs and total costs. Drug costs accounted for the largest proportion, at 54.35%. Therefore, the cost of hypertension medication was influenced by age and the number of comorbidities. Meanwhile, the total cost was influenced by the number of comorbidities